Who Was Basilius Hyacinthius Vilnensis, the Author of Panegyricus in excidium Polocense (Padua, 1580)? An Attempt at Authorship Attribution - Antanavičius, Darius (Senoji Lietuvos literatūra, 2019)
The study deals with a book under the title Panegyricus in excidium Polocense published by Basilius Hyacinthius Vilnensis in Padua (Italy) in 1580. Тhe book was dedicated to the recapture of the city of Polotsk (Полацк in Belarusian) by Stephen Báthory, King of Poland and Grand Duke of Lithuania, in 1579. The author concealed his real identity under the name Basilius Hyacinthius Vilnensis. The objective of the paper is to attempt to reveal the true name of the author. At the beginning, the conclusion is drawn that the first name, Basilius, is a Latinized form of the Slavic name Vasilij, Vasil’, Wasyl etc., while the second one, Hyacinthius, was a simple translation of the patronimic form of the name Hyacinthus, i. e., a son of Hyacinth. Subsequently, an effort is made to match these names with a real person who lived in the second half of the sixteenth century in Vilnius. After preliminary remarks on scarce material concerning the history of Vilnius during the period (due to colossal archival losses suffered in the middle of the seventeenth century) and from the issues of reliability of the resulting conclusions and results of research (when various subjective speculations are possible), the present study comes up with the hypothesis that Basilius Hyacinthius was Basil Jatskievich or Jatskovich (Slav. Василий Яцкевич / Яцкович). He must have been a son of Theodore Jatskievich or Jatskovich Vielkovich (Slav. Фёдор Яцкевич / Яцкович Велкoвич), a burgomaster of Vilnius active during the period of 1556-1580. At the end of the study, some potential directions for further investigation and argumentation of the hypothesis are proposed.